Patient-specific numerical investigation of the correction of cervical kyphotic deformity based on a retrospective clinical case - Wu, Tianchi; Chen, Hongyu; Sun, Yu; Xia, Tian; Zhou, Feifei; Lu, William W. (Frontiers in Bioengineering and Biotechnology, 2022)
Little research has been reported on evaluating the safety of the fixation construct in cervical kyphosis correction. In this study, we proposed a principal-strain criterion to evaluate the safety of the fixation construct and validated the modelling method against a retrospective case of anterior cervical discectomy fusion (ACDF). From C2 to T2 vertebra bodies and fixation instruments were reconstructed and positioned as per postoperative computed tomography (CT) scans. Head weight (HW) and various moments estimated from isometric strength data were imposed onto the C2. The postoperative stability of non-surgical segments, deformation surrounding screw trajectories and contact slipping on zygapophysial joints was analyzed. The model was validated against the reality that the patient has a good fusion and deformity correction. The ACDF restricted the range of motions (ROMs) of cervical segments and lent stability to vertebra fusion, no failure was found in the finite element (FE) model of cervical vertebrae. Deformation surrounding screw trajectories concentrated to lateral sides of trajectories, recommending that the shape of anterior cervical plate conforming the curvature of the vertebra and screws fully inserted into vertebrae reduce the deformation concentration around screw trajectories.